The New Myth: Frederic Spiegelberg and the Rise of a Whole Earth, 1914-1968. - Kabil, Ahmed M. (Integral Review: A Transdisciplinary & Transcultural Journal for New Thought, Research, & Praxis, 2012)
The present article provides, through the life and teachings of a little-known German scholar of religions named Frederic Spiegelberg (1897-1994), a novel account of some of the unique historical and intellectual developments that converged in the San Francisco Bay Area in the mid twentieth century and subsequently informed and enabled many of the defining chapters of recent global history. Separately, these developments are known as the dissemination in the West of Asian religious perspectives and practices, the San Francisco Renaissance, the rise of the counterculture, the widespread blossoming of environmental awareness, and the information age revolution. Together, they comprise The New Myth: synchronous with and in reaction to the planetary spread of technology and the global experiential horizons such technology discloses, a constellation of holistic integral thought emerged in various domains in the West that was characterized above all by a spatiotemporal emphasis on the 'Here and Now' and the realization of unity through the recognition and transcendence of polarity. The origins, afterlives, and implications of this constellation of thought are only now being discerned. The story of Professor Frederick Spiegelberg's life-little known and largely forgotten-functions as the conduit through which the New Myth's historical and intellectual contours are traced and thereby rendered intelligible.